Intergenerational transmission of 'religious capital': evidence from Spain - Pablo Bra\~nas-Garza; Shoshana Neuman (Institute for the Study of Labor (IZA), 2006)
The paper examines intergenerational transmission of 'religious capital' from parents to their offspring, within an economic framework of a production function of 'religiosity' where parental inputs serve as factors of production. A sample of Catholic Spaniards who grew up in Catholic households is used for the empirical study. A rich unique data base is employed with data on several aspects of religiosity: two dimensions of the individual's religiosity - mass attendance (6 levels) and prayer (11 levels); information on the mother's and father's church attendance when the respondent was a child (9 levels) as well as the respondent's mass participation at the age of 12. The use of detailed religiosity measures (rather than one dichotomous variable, e.g. goes to church-yes/no; practicing Catholic - yes/no), facilitates a more sophisticated analysis with robust conclusions. A theoretical framework is followed by stylized facts on household composition. Then the effect of the parents' input on respondent's religiosity is examined - first using cross-tabulation and then using Ordered Logit regression. The inputs of the parents are proxied by the mother's and father's intensity of church attendance when the respondent was a child. The output (respondent's religiosity) is measured using detailed data on mass attendance and prayer. Exposure to mass services during childhood and socio-economic variables are also considered. All in all we find that parental religious inputs significantly affect individuals' religiosity BUT the route of intergenerational transmission is from mother to daughter and from father to son. Women are not affected by paternal religiosity and men are unaffected by maternal religiosity. Current religiosity is also affected by own exposure to mass services during childhood - own experience has a more pronounced effect on the private/intimate activity of prayer than on the social/public activity of church attendance. Current mass participation is more affected by parental than by own mass attendance during childhood.
Keywords: Z12; J12; J13; D13; 330; religious capital; Catholic; church attendance; prayer; intergenerational transmission; production; Spain